A Conformational Restriction Strategy for the Control of CRISPR/Cas Gene Editing with Photoactivatable Guide RNAs. (22nd December 2022) - Sun, Ying‐Jie; Chen, Wen‐Da; Liu, Ji; Li, Jun‐Jin; Zhang, Yu; Cai, Wei‐Qi; Liu, Li; Tang, Xin‐Jing; Hou, Jian; Wang, Ming; Cheng, Liang
Abstract: The CRISPR/Cas system is one of the most powerful tools for gene editing. However, approaches for precise control of genome editing and regulatory events are still desirable. Here, we report the spatiotemporal and efficient control of CRISPR/Cas9‐ and Cas12a‐mediated editing with conformationally restricted guide RNAs (gRNAs). This approach relied on only two or three pre‐installed photo‐labile substituents followed by an intramolecular cyclization, representing a robust synthetic method in comparison to the heavily modified linear gRNAs that often require extensive screening and time‐consuming optimization. This tactic could direct the precise cleavage of the genes encoding green fluorescent protein (GFP) and the vascular endothelial growth factor A (VEGFA) protein within a predefined cutting region without notable editing leakage in live cells. We also achieved light‐mediated myostatin ( MSTN ) gene editing in embryos, wherein a new bow‐knot‐type gRNA was constructed with excellent OFF/ON switch efficiency. Overall, our work provides a significant new strategy in CRISPR/Cas editing with modified circular gRNAs to precisely manipulate where and when genes are edited. Abstract : We report on the discovery and development of conformationally restricted guide RNA, a head‐to‐tail cyclized molecule that can be easily prepared with only two or three modification sites. This is a superior approach for the spatiotemporal control of CRISPR/Cas editing, which has enabled the precise cleavage of exogenous genes at a predefined cutting region without notable editing leakages in live cells and in embryos.